Identifikasi Karakteristik Teknik Subgrade Jalan : (Studi Kasus Jalan Raya Tanak Awu-Pengembur, Lombok Tengah) - Heni Pujiastuti; Adryan Fitrayudha; Adiman Fariyadin; Hafiz Hamdani (Institut Teknologi Bandung, 2023)
Abstract The purpose of this research is to describe the results of the identification of the technical characteristics of the Tanak Awu-Pengembur Road subgrade, including mineralogy, physical characteristics, mechanical characteristics, and hydromechanical characteristics, based on the results of experimental tests in the laboratory so that they can be input for related institutions. The results of mineralogical identification using the XRD method showed that the soil samples contained the minerals saponite, beidellite, and montmorillonite, which included in the expansive smectite-type clay mineral group. The results of physical characteristics identification stated that the soil sample had a plasticity index (PI) of 44.34%, a liquid limit (LL) of 72.21% according to the ASTM D-1883 method, Chen (1988), Raman (1967), Ladid and Lambe (1961) which categorized as soil with a very high degree of swelling. The results of mechanical and hydromechanical characteristics identification stated that the swelling value of the sample soil was 5.539% (CBR test results) was classified as expansive soils. The results of mechanical identification stated that the design value of the California Bearing Ratio (CBR) soaked soil sample was 2%. The design value of CBR soaked has met the minimum requirements as a road subgrade. However, for expansive soil subgrades, the CBR value needs to be increased to greater than 6% with subgrade improvement use cement or selected backfill material with a minimum thickness of 600 mm (MDP 2017). Based on SWCC, the clay soil sample has an AEV value of 600 kPa while the residual suction (Sr) value not be identified. Keywords : Expansive clay, CBR, swelling-shrinkage, matric suction, AEV